Analisis Disparitas Ekonomi Wilayah Jabodetaek Pada Masa Pandemi Covid 19 - Taufik Hidayadi; Achmad Mukafi Niam (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
Disparity and the economy has become an important discussion for economic scientists and development policy makers. Both as an evaluation material for planning and as part of the implementation of the development itself. Currently, with the Covid-19 pandemic, economic problems is a serious concern. This study tries to look at the economic conditions in the Jabodetabek area during the 2020 pandemic with the Williamson index and Klassen Typology. In 2020, it can be seen that the Williamson Index, when the pandemic occurred, decreased from 0.71 to 0.66 or decreased by 0.05 points, as a result of cross section data at the end of the year. This could be due to a decrease in income in certain groups or the type of data used. In the Klassen typology calculation, most of the regions are in quadrant III, it is possible that most regions experienced a significant decrease in GRDP. Quadrant IV is mostly filled by cities in Jakarta minus East Jakarta. This quadrant is possible due to the heavy burden of minus growth with economic conditions experiencing contraction due to tightening activities by the government. Initial research on the economy is expected to be continued with deeper research for economic evaluation after the Covid 19 pandemic and the end of development planning in Jabodetabek.